Thirteen ghosts - Adler, Gilbert; Silver, Joel.; Zemeckis, Robert, 1952-; Stevens, Neal Marshall; D'Ovidio, Richard; Beck, Steve; Shalhoub, Tony, 1953-; Davidtz, Embeth, 1966-; Lillard, Matthew, 1970-; Elizabeth, Shannon; Roberts, Alec.; Bourne, J. R.; et al. ([United States] : Warner Home Video, 2002)
After a tragedy strikes, a family discovers that the home they've inherited from an eccentric uncle is inhabited by sinister phantoms. Once the 12 ghosts are unlocked from the basement of the house, there is only the need for one more fresh ghost to fulfil an evil prophesy. Which member of the family will it be?
Special features: "Thirteen ghosts revealed", a behind-the -scenes documentary; feature length commentary by production designer Sean Hargreaves and creator of special make-up effects Howard Berger; "Ghost files", 12 vignettes profiling the ghosts; music montage; full frame (1.85:1) version.
Director of photography, Gale Tattersall ; editors, Derek G. Brechin, Edward A. Warschilka ; music, John Frizzell ; costume designer, Jenni Gullett ; production designer, Sean Hargreaves ; special make-up effects, Howard Berger ... [et al.]
Tony Shalhoub, Embeth Davidtz, Matthew Lillard, Shannon Elizabeth, Alec Roberts, J.R. Bourne, Rah Digga, F. Murray Abraham.
MPAA rating: R.
DVD, Dolby digital 5.1 audio.
Closed-captioned for the hearing impaired.
Keywords: Ghost plays; Horror films; Video recordings for the hearing impaired